A multi-process combined polishing method for additive manufacturing of metal pipe samples

CN122913954APending Publication Date: 2026-10-16BEIJING HANGXING MACHINERY MFG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611151420.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]鉴于上述的分析,本发明旨在提供一种增材制造金属管路试样的多工艺组合抛光方法,用以解决现有抛光方法易产生加工应力、适应性差、表面初始缺陷的修复能力不足、抛光效率低、无法同时满足不同特性材料加工的问题中的至少一个

Benefits of technology

[0015]与现有技术相比,本发明至少可实现如下有益效果之一:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the technical field of additive manufacturing post-processing, and particularly relates to a multi-process combined polishing method for an additive manufacturing metal pipeline sample, which is used to solve at least one of the problems that the existing polishing method is prone to processing stress, has poor adaptability, has insufficient repair capacity for surface initial defects, has low polishing efficiency, and cannot simultaneously meet the processing of different characteristic materials. The polishing method comprises the following steps: pretreatment; two-phase flow rough polishing by using a two-phase flow; abrasive flow fine polishing by using an abrasive flow; and electrochemical final polishing. The average particle size of second abrasive particles in the abrasive flow is smaller than the average particle size of first abrasive particles in the two-phase flow. The polishing method simultaneously realizes defect removal, complex inner cavity processing, high-efficiency polishing of high-strength materials, stress-free surface flattening, and adaptation to titanium alloy, aluminum alloy, high-temperature alloy and various additive manufacturing metals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of additive manufacturing post-processing technology, and in particular to a multi-process combined polishing method for additive manufacturing metal pipeline samples. Background Technology

[0002] Additive manufacturing technologies (such as selective laser melting and electron beam melting) are widely used in aerospace, medical devices, and high-end equipment due to their rapid prototyping and complex structure manufacturing capabilities. However, during the additive manufacturing process, defects such as adhesive powder, molten spheres, and microcracks are prone to exist on the inner surface of metal pipe samples, resulting in high inner surface roughness, which seriously affects the fatigue performance, corrosion resistance, and assembly accuracy of the samples.

[0003] Existing polishing technologies suffer from problems such as easy generation of processing stress, poor adaptability, insufficient ability to repair initial surface defects, low polishing efficiency, and inability to meet the processing needs of materials with different properties. Summary of the Invention

[0004] Based on the above analysis, the present invention aims to provide a multi-process combined polishing method for additive manufacturing metal pipe samples, in order to solve at least one of the problems of existing polishing methods, such as easy generation of processing stress, poor adaptability, insufficient ability to repair initial surface defects, low polishing efficiency, and inability to simultaneously meet the processing requirements of materials with different properties.

[0005] On one hand, the present invention provides a multi-process combined polishing method for additive manufacturing metal pipe samples, comprising the following steps: S1. Pre-treatment of additive manufacturing metal pipeline samples to obtain initial samples; S2. Two-phase flow rough polishing is performed using two-phase flow to obtain a rough polished sample; S3. Use abrasive flow to perform abrasive flow fine polishing to obtain a finely polished sample; S4. Perform electrochemical final polishing to obtain the final sample; the average particle size of the second abrasive in the abrasive flow is smaller than the average particle size of the first abrasive in the two-phase flow.

[0006] Furthermore, the two-phase flow consists of a first abrasive grain and water, wherein the first abrasive grain in the two-phase flow includes one or more of boron nitride, aluminum oxide, and diamond.

[0007] Furthermore, the mass percentage of the first abrasive grain in the two-phase flow is 10% to 22%; And / or, the average particle size of the first abrasive grain in the two-phase flow is 0.05 to 0.3 mm.

[0008] Furthermore, the water pressure for the two-phase flow rough polishing in S2 is 5-12 MPa; And / or, the processing time for the two-phase flow rough polishing in S2 is 10-20 min.

[0009] Furthermore, the abrasive flow includes a second abrasive grain and a carrier; the second abrasive grain in the abrasive flow includes silicon carbide and / or aluminum oxide.

[0010] Furthermore, the average particle size of the second abrasive grain in the abrasive flow is 10-28 μm; And / or, the mass percentage of the second abrasive grain in the abrasive flow is 40% to 60%.

[0011] Furthermore, the pressure of the abrasive flow polishing in S3 is 2~5MPa; And / or, the flow rate of the abrasive flow polishing in S3 is 8-15 m / s; And / or, the processing time for abrasive flow polishing in S3 is 15~25 min.

[0012] Furthermore, the electrochemical final polishing process in S4 includes: using the finely polished sample as the anode and the lead plate as the cathode, immersing it in the electrochemical polishing solution for electrolysis.

[0013] Furthermore, the electrochemical polishing solution comprises sulfuric acid, phosphoric acid, citric acid, and water; And / or, the electrolysis temperature is 30-60℃; And / or, the current density of the electrolysis is 8~25 A / dm³. 2 ; And / or, the electrolysis time is 5~15 min.

[0014] Furthermore, the final sample exhibits a roughness reduction rate of ≥97% relative to the initial sample.

[0015] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects: 1. Multi-process synergy and strong adaptability: This invention solves the problem of poor adaptability of single processes by performing a combination of two-phase flow rough polishing (removing macroscopic defects), abrasive flow fine polishing (repairing microscopic protrusions), and electrochemical final polishing (stress-free bright finish). It is suitable for the precise polishing of different materials such as titanium alloys, high-temperature alloys, and aluminum alloys with different properties.

[0016] 2. Efficiency and quality balance: The pretreatment of two-phase flow coarse polishing and abrasive flow fine polishing effectively shortens the electrochemical final polishing time, avoids material loss caused by excessive electrolysis, and is suitable for mass production.

[0017] 3. By controlling the average particle size of the first abrasive grain in the two-phase flow and the second abrasive grain in the abrasive flow, as well as the process parameters in each polishing process, this invention avoids excessive cutting of the additive manufacturing metal pipeline sample while effectively reducing its roughness.

[0018] 4. Significantly improved surface roughness: The surface roughness of the final sample obtained by the method of the present invention is less than 0.5 μm, which is more than 97% lower than that of the initial sample. Moreover, there are no defects such as processing stress and microcracks on the surface, which effectively improves the fatigue performance and corrosion resistance of the final sample.

[0019] In this invention, the above-described technical solutions can be combined with each other to achieve more preferred combinations. Other features and advantages of this invention will be set forth in the following description, and some advantages may become apparent from the description or be learned by practicing the invention. The objectives and other advantages of this invention can be realized and obtained through the specific points highlighted in the description. Detailed Implementation

[0020] The following examples, taken together with the embodiments of the present invention, are used to illustrate the principles of the invention and are not intended to limit the scope of the invention.

[0021] Among existing polishing technologies, mechanical polishing can reduce roughness, but it easily generates processing stress and has poor adaptability to complex structural samples; electrochemical polishing alone can achieve stress-free polishing, but its ability to repair initial surface defects is limited; abrasive flow polishing is suitable for complex structures such as internal flow channels, but its polishing efficiency is low for high-strength materials such as titanium alloys and high-temperature alloys. In addition, different metal materials have large differences in physicochemical properties (such as the high hardness of titanium alloys and the high-temperature resistance of high-temperature alloys), and a single polishing process cannot simultaneously meet the surface quality requirements of two types of materials.

[0022] Based on this, embodiments of the present invention disclose a multi-process combined polishing method for additive manufacturing metal pipe samples, comprising the following steps: S1. Pre-treatment of additive manufacturing metal pipeline samples to obtain initial samples; S2. Two-phase flow rough polishing is performed using two-phase flow to obtain a rough polished sample; S3. Use abrasive flow to perform abrasive flow fine polishing to obtain a finely polished sample; S4. Perform electrochemical final polishing to obtain the final sample; the average particle size of the second abrasive grain in the abrasive flow is smaller than the average particle size of the first abrasive grain in the two-phase flow.

[0023] In the above system, the three polishing processes work synergistically and are indispensable. Two-phase flow rough polishing is performed first to quickly remove original defects such as printing lines and protrusions, compensating for insufficient defect repair capabilities in subsequent polishing. Omitting this step would leave residual surface imperfections on the final sample. The intermediate abrasive flow fine polishing precisely refines the irregular internal flow channels of the additively manufactured metal pipeline sample, efficiently eliminating surface undulations caused by the two-phase flow rough polishing. Omitting this step and proceeding directly to electrochemical polishing can easily lead to uneven corrosion and color differences. The final electrochemical polishing eliminates residual stress generated by the previous two fluid processing steps, achieving a stress-free mirror finish. Reversing the order of these polishing steps would introduce stress again during the mechanical processing of the two-phase flow rough polishing and abrasive flow fine polishing. The three processes work in an orderly manner, simultaneously achieving defect removal, complex internal cavity machining, efficient polishing of high-strength materials, and stress-free surface leveling. This system is suitable for various additively manufactured metal pipelines such as titanium alloys, aluminum alloys, and high-temperature alloys, overcoming the comprehensive performance deficiencies of single polishing technologies.

[0024] Furthermore, the additive manufacturing metal pipeline test specimens include one or more of the following: titanium alloy additive manufacturing pipeline test specimens, nickel-based high-temperature alloy additive manufacturing pipeline test specimens, and aluminum alloy additive manufacturing pipeline test specimens.

[0025] Furthermore, the additive manufacturing metal pipeline samples include those formed by selective laser melting and / or electron beam melting. Compared to ordinary metal pipeline samples, due to the limitations of the additive manufacturing process, the inner surface of additive manufacturing metal pipeline samples is prone to defects such as adhesive powder, molten spheres, and microcracks, resulting in higher surface roughness. The polishing method of this application is applicable to additive manufacturing metal pipeline samples formed by selective laser melting and / or electron beam melting, effectively reducing their roughness.

[0026] Furthermore, the pretreatment process for the additive manufacturing metal pipeline sample in S1 includes ultrasonic cleaning of the additive manufacturing metal pipeline sample.

[0027] Furthermore, the ultrasonic cleaning fluid used in ultrasonic cleaning includes water and a cleaning agent. The mass percentage of the cleaning agent in the ultrasonic cleaning fluid is 5% to 10%, for example, 5%, 6%, 7%, 8%, 9%, or 10%. If the cleaning agent content is too low, the printing powder on the surface of the additive manufacturing metal pipe sample and the oil stains in the inner cavity will not be thoroughly cleaned, and the residual impurities will contaminate the subsequent two-phase flow and electrochemical polishing fluid. If the cleaning agent content is too high, the cleaning agent residue will increase, which will easily form a film on the inner wall of the additive manufacturing metal pipe sample, reducing the subsequent polishing and leveling effect and increasing the processing cost.

[0028] Furthermore, the pH of the ultrasonic cleaning solution is 7.0~8.8, such as 7.0, 7.5, 8.0, 8.5, 8.8, which is beneficial for removing oil and powder impurities from the surface of additive manufacturing metal pipeline samples and avoids corrosion of additive manufacturing metal pipeline samples caused by excessively high or low pH.

[0029] Specifically, the cleaning agent can be a conventional cleaning agent in the field, such as Terrent SR-820I.

[0030] Furthermore, during the ultrasonic cleaning process, the ultrasonic frequency is 28~40kHz (e.g., 28kHz, 30kHz, 33kHz, 35kHz, 38kHz, 40kHz or any combination thereof), the power is 25~40W (e.g., 25W, 30W, 35W, 40W or any combination thereof), the temperature is 40~55℃ (e.g., 40℃, 45℃, 50℃, 55℃ or any combination thereof), and the time is 5~15min (e.g., 5min, 8min, 10min, 13min, 15min or any combination thereof), which is beneficial for removing oil and powder impurities from the surface of additively manufactured metal pipe samples.

[0031] Furthermore, the roughness of the initial sample is 5~20μm, for example 5μm, 10μm, 15μm, 20μm.

[0032] Furthermore, the two-phase flow in S2 adopts a water-based solid-liquid two-phase flow, which consists of a first abrasive particle and water.

[0033] Furthermore, the first abrasive grain in the two-phase flow includes one or more of boron nitride, aluminum oxide, and diamond. Among them, aluminum oxide is the main cutting phase in the rough polishing of the two-phase flow, boron nitride plays a lubricating and tear-preventing role, and diamond is specifically used to target hard agglomerates.

[0034] Preferably, when the additive manufacturing metal pipeline sample is an aluminum alloy additive manufacturing pipeline sample, the first abrasive particles in the two-phase flow include boron nitride and / or aluminum oxide.

[0035] For example, when the additive manufacturing metal pipeline sample is an aluminum alloy additive manufacturing pipeline sample, the first abrasive particles in the two-phase flow include, by mass percentage: 65%~75% boron nitride and the balance is aluminum oxide.

[0036] For example, when the additive manufacturing metal pipeline sample is a titanium alloy additive manufacturing pipeline sample, the first abrasive grain in the two-phase flow includes, by mass percentage: 70%~75% boron nitride, 5%~10% diamond, and the balance is aluminum oxide.

[0037] For example, when the additive manufacturing metal pipeline sample is a nickel-based high-temperature alloy additive manufacturing pipeline sample, the first abrasive grain in the two-phase flow includes, by mass percentage: 60%~65% boron nitride, 15%~20% diamond, and the balance is aluminum oxide.

[0038] Furthermore, the mass percentage of the first abrasive grain in the two-phase flow is 10% to 22%, for example, 10%, 13%, 15%, 18%, 20%, 22%.

[0039] Furthermore, the average particle size of the first abrasive grain in the two-phase flow is 0.05–0.3 mm, for example, 0.05 mm, 0.1 mm, 0.15 mm, 0.2 mm, 0.25 mm, or 0.3 mm. When the number of first abrasive grain types in the two-phase flow is greater than one, the average particle size of the first abrasive grain refers to the average particle size after mixing different types of first abrasive grains.

[0040] When the content of the first abrasive particles in the two-phase flow is too low and the particle size is too small, the impact force of the particles in the two-phase flow is weak, which will lead to insufficient removal efficiency of molten balls and interlayer steps. When the proportion of the first abrasive particles in the two-phase flow is too high and the particle size is too large, it is easy to cause deep scratches on the inner wall and uneven polishing of the inner wall of the sample, which is difficult to repair in subsequent processes.

[0041] Specifically, during the two-phase flow rough polishing in S2, the additive manufacturing metal pipeline sample can be fixed on the two-phase flow processing fixture.

[0042] Furthermore, the water pressure for rough polishing of the two-phase flow in S2 is 5-12 MPa, such as 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa, 10 MPa, 11 MPa, 12 MPa or any combination thereof. If the pressure is too low, the impact kinetic energy of the first abrasive grain in the two-phase flow is insufficient, the molten spheres and interlayer steps of the additive manufacturing metal pipeline sample are not completely removed, and the defects remain severely after rough polishing of the two-phase flow. If the pressure is too high, it is easy to cause over-cutting of the inner wall of the pipeline sample and produce deep scratches. Thin-walled pipelines also have the risk of deformation.

[0043] Furthermore, the processing time for two-phase flow rough polishing in S2 is 10-20 min, such as 10 min, 13 min, 15 min, 18 min, 20 min or any combination thereof. If the processing time is insufficient, the macroscopic defects of the additively manufactured metal pipeline sample will not be completely removed, which will significantly increase the subsequent polishing load. If the time is too long, the processing efficiency will be low, and it will also aggravate the wear of the inner wall and generate additional processing damage.

[0044] Preferably, when the additive manufacturing metal pipeline sample is a titanium alloy additive manufacturing pipeline sample or a nickel-based high-temperature alloy additive manufacturing pipeline sample, the mass percentage of the first abrasive grain in the two-phase flow is 16% to 22%. Titanium alloy and nickel-based high-temperature alloy are hard substrates. Using a higher proportion of the first abrasive grain is beneficial to stably remove the printing macroscopic defects of the additive manufacturing metal pipeline sample and provide a flat substrate for subsequent processes.

[0045] Preferably, when the additive manufacturing metal pipeline sample is a titanium alloy additive manufacturing pipeline sample or a nickel-based high-temperature alloy additive manufacturing pipeline sample, the water pressure for rough polishing of the two-phase flow in S2 is 8-12 MPa; the processing time for rough polishing of the two-phase flow in S2 is 15-20 min; and the average particle size of the first abrasive grain in the two-phase flow is 0.1-0.3 mm.

[0046] Titanium alloys and nickel-based superalloys have high hardness and hard surface agglomerates, requiring higher pressure, longer processing time, and larger abrasive grains for efficient removal of molten spheres and interlayer steps. If the pressure is too low, the processing time is insufficient, or the grain size is too small, the impact kinetic energy of the first abrasive grain is insufficient, making it difficult to remove hard defects. The roughness of the additively manufactured metal pipeline sample after two-phase flow rough polishing is high, which greatly increases the load on subsequent abrasive flow fine polishing. If the pressure is too high, the processing time is too long, or the grain size is too large, the high impact can easily form deep scratches on the inner wall of titanium alloys and nickel-based superalloys. The concentrated frictional heat during processing can cause surface oxidation and work hardening. Thin-walled pipelines also have the risk of impact deformation, and excessive cutting can cause excessive material loss.

[0047] Furthermore, when the additive manufacturing metal pipeline sample is an aluminum alloy additive manufacturing pipeline sample, the water pressure for rough polishing in the two-phase flow in S2 is 5-8 MPa; the processing time for rough polishing in the two-phase flow in S2 is 10-15 min; and the average particle size of the first abrasive grain in the two-phase flow is 0.05~0.1 mm.

[0048] Aluminum alloys are soft, highly ductile, and have poor impact and cutting resistance. Therefore, using the aforementioned combination of low pressure, short processing time, and fine first abrasive grains can remove minor surface textures and fine powder particles while avoiding excessive damage to the substrate. If the pressure is too low, the processing time is insufficient, or the first abrasive grain size is too small, the particle impact energy of the two-phase flow will be insufficient, resulting in incomplete removal of printing residue defects and excessive roughness of the rough polished sample. If the pressure is too high, the processing time is too long, or the first abrasive grain size is too large, the hard first abrasive grains can easily erode deep scratches and pits on the soft inner wall of the aluminum alloy, causing plastic deformation. This type of damage is difficult to completely repair in subsequent abrasive flow finishing polishing and electrochemical final polishing, severely reducing the surface uniformity and corrosion resistance of the pipeline.

[0049] Furthermore, the abrasive flow includes a second abrasive grain and a carrier, and the surface micro-protrusions are repaired through the shearing and grinding action of the second abrasive grain.

[0050] Furthermore, the second abrasive grain in the abrasive stream comprises silicon carbide and / or aluminum oxide.

[0051] Furthermore, the average particle size of the second abrasive grain in the abrasive flow is 10-28 μm, for example, 10 μm, 13 μm, 15 μm, 18 μm, 20 μm, 23 μm, 25 μm, and 28 μm. If the particle size is too small, the shearing and grinding force is insufficient, and the fine undulations left by the two-phase flow rough polishing cannot be eliminated; if the particle size is too large, it is easy to generate fine cutting marks, increasing the pressure of the electrochemical final polishing process. The two-phase flow uses millimeter-sized first abrasive grains of 0.05~0.3 mm to peel off macroscopic large defects such as molten spheres and interlayer steps by high-pressure impact; the abrasive flow uses micrometer-sized second abrasive grains of 10~28 μm for low-speed shearing and leveling of microscopic protrusions.

[0052] Furthermore, the mass percentage of the second abrasive grain in the abrasive flow is 40% to 60%, for example, 40%, 45%, 50%, 55%, or 60%.

[0053] When the content of the second abrasive grain in the abrasive flow is too low, there are insufficient grinding particles, resulting in low efficiency in repairing the micro-protrusions of the coarsely polished sample; when the content of the second abrasive grain is too high, the fluidity of the abrasive flow deteriorates, narrow-channel samples are prone to clogging, and the polishing uniformity decreases.

[0054] Furthermore, the carrier is a viscous paste. The viscous paste carrier can uniformly coat the second abrasive grains and adhere to the irregular inner wall of the pipeline, continuously and stably generating shearing and grinding action, while removing grinding debris and buffering processing stress.

[0055] Furthermore, the carrier contains water and a thickener, which includes one or more of cellulose and guar gum. The mass percentage of the thickener in the abrasive stream is 1.5% to 3%, for example, 1.5%, 1.8%, 2%, 2.3%, 2.5%, 2.8%, and 3%. If the amount of thickener added is too low, the carrier viscosity is insufficient, and the second abrasive grain is prone to sedimentation and stratification. If the amount of thickener added is too high, the carrier viscosity is too high, the abrasive stream transport resistance increases, and the inner cavity edges and corners are not properly ground.

[0056] Furthermore, the pressure for abrasive flow fine polishing in S3 is 2~5MPa, for example, 2MPa, 3MPa, 4MPa, 5MPa or any combination thereof; if the pressure is too low, the abrasive flow will not adhere to the pipe wall sufficiently, the shearing and grinding force of the abrasive flow will be weak, and the micro-undulations left by the two-phase flow rough polishing will not be effectively smoothed; if the pressure is too high, it will easily cause plastic deformation of the additive manufacturing metal pipe sample or fine cutting scratches on the inner wall, and will also aggravate the heating and aging of the carrier in the abrasive flow.

[0057] Furthermore, the flow rate of the abrasive flow polishing in S3 is 8-15 m / s, for example, 8 m / s, 9 m / s, 10 m / s, 11 m / s, 12 m / s, 13 m / s, 14 m / s, 15 m / s or any combination thereof; when the flow rate is too low, the abrasive flow circulation is slow, the dead corners of the pipeline sample are not sufficiently polished, and the surface uniformity is poor; when the flow rate is too high, the second abrasive in the abrasive flow rubs violently against the pipe wall, which easily leads to over-polishing, local dimensional deviations, and accelerated wear of the second abrasive.

[0058] Furthermore, the processing time for abrasive flow polishing in S3 is 15~25min, for example, 15min, 18min, 20min, 23min, 25min or any combination thereof; if the processing time is insufficient, the micro-protrusions will not be properly repaired, and the roughness of the polished sample will be too high; if the processing time is too long, the processing efficiency will decrease, and continuous grinding will deepen the fine texture on the surface, increasing the difficulty of subsequent electrochemical final polishing.

[0059] Furthermore, when the additive manufacturing metal pipeline sample is a titanium alloy additive manufacturing pipeline sample or a nickel-based high-temperature alloy additive manufacturing pipeline sample, the pressure of abrasive flow polishing in S3 is 3~5MPa; the flow rate of abrasive flow polishing in S3 is 10-15m / s; and the processing time of abrasive flow polishing in S3 is 20~25min. If the pressure and flow rate are below the lower limit or the processing time is insufficient, the shearing and grinding force of the abrasive flow is weak and cannot fully remove the micro-peaks and valleys, resulting in excessively high roughness of the polished sample. If the pressure and flow rate are too high or the processing time is too long, the continuous high-intensity micro-cutting of the abrasive flow will generate fine and uniformly deep grinding scratches on the pipe wall, significantly increasing the leveling pressure of the subsequent electrochemical final polishing, and at the same time aggravating the heating and aging of the abrasive flow.

[0060] Furthermore, when the additive manufacturing metal pipeline sample is an aluminum alloy additive manufacturing pipeline sample, the pressure of the abrasive flow polishing in S3 is 2~3MPa; the flow rate of the abrasive flow polishing in S3 is 8~12m / s; and the processing time of the abrasive flow polishing in S3 is 15~20min. If the above parameters are too low, the shearing effect of the abrasive flow is insufficient, the minor surface undulations are not thoroughly repaired, and the roughness of the polished sample cannot be effectively reduced. If the above parameters are too high, the abrasive flow will produce irreversible plastic indentations and embedded scratches on the soft pipe wall. This type of plastic damage is difficult to completely eliminate by electrochemical polishing, ultimately reducing the uniformity and corrosion resistance of the pipeline inner wall.

[0061] Furthermore, the electrochemical final polishing process in S4 includes: using the finely polished sample as the anode and the lead plate as the cathode, immersing it in the electrochemical polishing solution for electrolysis.

[0062] Furthermore, the electrochemical polishing solution includes sulfuric acid, phosphoric acid, citric acid, and water.

[0063] Furthermore, the sulfuric acid concentration in the electrochemical polishing solution is 150-200 g / L, such as 150 g / L, 160 g / L, 170 g / L, 180 g / L, 190 g / L, 200 g / L, or any combination thereof. If the sulfuric acid concentration is too low, the dissolving and leveling ability of the electrochemical polishing solution will be insufficient, and if the sulfuric acid concentration is too high, it will easily cause excessive corrosion, resulting in pitting on the final sample.

[0064] Furthermore, the phosphoric acid concentration in the electrochemical polishing solution is 300-400 g / L, such as 300 g / L, 330 g / L, 350 g / L, 380 g / L, 400 g / L, or any combination thereof. If the phosphoric acid concentration is too low, a uniform passivation film cannot be formed, leading to over-electrochemical polishing of the finely polished sample and causing corrosion. If the phosphoric acid concentration is too high, the viscosity of the electrochemical polishing solution increases and the polishing rate decreases.

[0065] Furthermore, the concentration of citric acid in the electrochemical polishing solution is 20-30 g / L, such as 20 g / L, 23 g / L, 25 g / L, 28 g / L, 30 g / L, or any combination thereof. A citric acid concentration within the above range is beneficial for inhibiting local pitting corrosion and improving the uniformity of the final sample surface. If the concentration is too low, it cannot effectively inhibit local pitting corrosion, and if the concentration is too high, it will reduce the electrolysis efficiency and prolong the processing time.

[0066] Furthermore, the electrolysis temperature is 30-60℃, such as 30℃, 40℃, 50℃, 60℃ or any combination thereof. When the temperature is too low, the reaction ions in the final electrochemical polishing process are less active, and the leveling and brightening rate is slow. When the temperature is too high, the sample corrosion is aggravated, and pitting and color difference are likely to occur.

[0067] Furthermore, the current density for electrolysis is 8~25 A / dm³. 2 For example, 8A / dm 2 10A / dm 2 15A / dm 2 20A / dm 2 25A / dm 2 If the current density is too low, the electrolytic leveling effect will be weak, and the final sample surface will not be bright enough; if it is too high, it will cause severe gas evolution, and the final sample will be locally over-corroded, resulting in pitting on the inner wall.

[0068] Furthermore, the electrolysis time is 5 to 15 minutes, for example, 5 minutes, 8 minutes, 10 minutes, 13 minutes, 15 minutes, or any combination thereof.

[0069] Furthermore, when the additive manufacturing metal pipeline sample is a titanium alloy additive manufacturing pipeline sample, the electrolysis temperature is 40-50℃; the electrolysis current density is 15~20A / dm²; and the electrolysis time is 8~12min. A dense oxide film is easily formed on the surface of the titanium alloy. When the electrolysis temperature, current density, and electrolysis time are within the above range, the oxide film can be stably dissolved and the surface can be uniformly leveled. When the electrolysis temperature, current density, and electrolysis time are too low, the oxide film is not completely removed, and the final sample has poor gloss. When the electrolysis temperature, current density, and electrolysis time are too high, local pitting corrosion is likely to occur, and the final sample surface will turn gray.

[0070] Furthermore, when the additive manufacturing metal pipeline sample is a nickel-based high-temperature alloy additive manufacturing pipeline sample, the electrolysis temperature is 50-60℃; the electrolysis current density is 20~25A / dm²; and the electrolysis time is 10~15min. The residual scratches after polishing of nickel-based alloys are deeper, requiring higher electrolysis temperature and current density as well as a longer electrolysis time to achieve sufficient leveling of the final sample. If the above parameters are too low, the texture of the polished sample cannot be eliminated; if the above parameters are too high, intergranular corrosion is prone to occur, and the surface roughness uniformity of the final sample deteriorates.

[0071] Furthermore, when the additive manufacturing metal pipeline sample is an aluminum alloy additive manufacturing pipeline sample, the electrolysis temperature is 30~40℃; the electrolysis current density is 8~12A / dm²; and the electrolysis time is 5~8min. Aluminum alloy has high chemical activity, and using a lower electrolysis temperature and current density and a shorter electrolysis time can avoid over-corrosion of the final sample. If the above parameters are too low, the final sample will not have a bright effect. If the above parameters are too high, the additive manufacturing metal pipeline sample will be quickly dissolved, resulting in dimensional deviations and pitting on the inner wall.

[0072] Furthermore, the roughness of the final sample is 0.05~0.5μm, for example 0.05μm, 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm.

[0073] The method in this embodiment of the invention is beneficial to reduce the surface roughness of additive manufacturing metal pipeline samples. Specifically, after two-phase flow coarse polishing, abrasive flow fine polishing, and electrochemical final polishing, the roughness of the final sample relative to the initial sample is reduced by ≥97%.

[0074] The present invention will be further described below through specific embodiments.

[0075] Example 1 The additive manufacturing metal pipeline sample was selected from TC4 titanium alloy samples formed by selective laser melting. The samples were ultrasonically cleaned for 10 minutes with ultrasonic cleaning solution (pH value 8.0). The ultrasonic frequency was 40kHz, the power was 30W, the temperature was 45℃, and the mass percentage of the cleaning agent (Tairunte SR-820I) in the ultrasonic cleaning solution was 8%, with the remainder being water. The additively manufactured metal pipeline sample was fixed on a two-phase flow processing fixture for two-phase flow rough polishing. The two-phase flow, by mass percentage, consisted of 20% first abrasive particles and the remainder was water. The first abrasive particles were a mixture of boron nitride, aluminum oxide, and diamond in a mass ratio of 7:2:1, with an average particle size of 0.2 mm. The water pressure for two-phase flow rough polishing was 10 MPa, and the processing time was 18 min. Abrasive flow polishing: The abrasive flow, by mass percentage, includes: 50% silicon carbide (average particle size 18μm), 47% deionized water, and 3% guar gum. The pressure of abrasive flow polishing is 4MPa, the flow rate is 12m / s, and the time is 22min. Electrochemical final polishing: The finely polished sample obtained after abrasive flow polishing is used as the anode, and a lead plate is used as the cathode. The sample is immersed in an electrochemical polishing solution for electrolysis to obtain the final sample. The electrochemical polishing solution consists of sulfuric acid, phosphoric acid, citric acid, and deionized water, with sulfuric acid concentrations of 180 g / L, phosphoric acid concentrations of 350 g / L, and citric acid concentrations of 25 g / L. The electrolysis temperature is 45℃, and the current density is 18 A / dm³. 2 The electrolysis time is 10 minutes.

[0076] Example 2 The additive manufacturing metal pipeline sample was selected from the GH4099 high-temperature alloy sample formed by electron beam melting. It was ultrasonically cleaned for 12 minutes with ultrasonic cleaning fluid (pH value 8.0); the ultrasonic frequency was 40kHz, the power was 30W, the temperature was 45℃, and the mass percentage of the cleaning agent (Tairunte SR-820I) in the ultrasonic cleaning fluid was 8%, with the remainder being water. The additively manufactured metal pipeline sample was fixed on a two-phase flow processing fixture for two-phase flow rough polishing. The two-phase flow adopted was a water-based solid-liquid two-phase flow, which included 20% of the first abrasive particles by mass percentage, with the balance being water. The first abrasive particles were a mixture of boron nitride, aluminum oxide, and diamond in a mass ratio of 6:2:2, with an average particle size of 0.25 mm (250 μm). The water pressure for two-phase flow rough polishing was 10 MPa, and the processing time was 18 min. Abrasive flow polishing: The abrasive flow, by mass percentage, includes: 50% silicon carbide (average particle size 22μm), 47% deionized water, and 3% guar gum. The pressure of abrasive flow polishing is 4MPa, the flow rate is 13m / s, and the processing time is 23min. Electrochemical final polishing: The finely polished sample obtained after abrasive flow polishing is used as the anode, and a lead plate is used as the cathode. The sample is placed in an electrochemical polishing solution for electrolysis to obtain the final sample. The electrochemical polishing solution consists of sulfuric acid, phosphoric acid, citric acid, and deionized water, with sulfuric acid concentrations of 190 g / L, phosphoric acid concentrations of 380 g / L, and citric acid concentrations of 28 g / L. The electrolysis temperature is 55℃, the current density is 22 A / dm², and the electrolysis time is 13 min.

[0077] Example 3 The additive manufacturing metal pipeline sample was an AlSi10Mg aluminum alloy sample formed by selective laser melting. It was ultrasonically cleaned for 8 minutes with an ultrasonic cleaning solution (pH 8.0). The ultrasonic frequency was 40 kHz, the ultrasonic power was 30 W, and the temperature was 45 ℃. The ultrasonic cleaning solution contained 8% by mass of cleaning agent (Tairunte SR-820I) and the remainder was water. The additively manufactured metal pipe sample was fixed on a two-phase flow processing fixture for two-phase flow rough polishing. The two-phase flow adopted was a water-based solid-liquid two-phase flow, which included 20% first abrasive particles and the balance being water by mass percentage. The first abrasive particles were a mixture of boron nitride and aluminum oxide in a mass ratio of 7:3, with an average particle size of 80μm (0.08mm). The water pressure for two-phase flow rough polishing was 7MPa, and the processing time was 12min. Abrasive flow polishing: The abrasive flow, by mass percentage, includes: 50% silicon carbide (average particle size 14μm), 47% deionized water, and 3% guar gum. The pressure for abrasive flow polishing is 2.5MPa, the flow rate is 10m / s, and the processing time is 18min. Electrochemical final polishing: The finely polished sample obtained after abrasive flow polishing is used as the anode, and a lead plate is used as the cathode. The sample is immersed in an electrochemical polishing solution for electrolysis to obtain the final sample. The electrochemical polishing solution consists of sulfuric acid, phosphoric acid, citric acid, and deionized water, with sulfuric acid concentrations of 160 g / L, phosphoric acid concentrations of 320 g / L, and citric acid concentrations of 22 g / L. The temperature is 35℃, and the current density is 10 A / dm³. 2 The electrolysis time is 6 minutes.

[0078] Example 4 The difference from Example 1 lies in the following conditions, while the other conditions remain the same as in Example 1.

[0079] The water pressure for two-phase flow rough polishing is 8 MPa, and the processing time is 15 min. Abrasive flow polishing: average silicon carbide particle size is 22μm, pressure is 3MPa, flow rate is 10m / s, and processing time is 20min; Electrochemical polishing: Electrolysis temperature 40℃, current density 15A / dm³ 2 The electrolysis time is 8 minutes.

[0080] Example 5 The difference from Example 1 lies in the following conditions, while the other conditions remain the same as in Example 1.

[0081] The water pressure for two-phase flow rough polishing is 12 MPa, and the processing time is 20 min. Abrasive flow polishing: average silicon carbide particle size is 14μm, pressure is 5MPa, flow rate is 15m / s, and processing time is 25min; Electrochemical final polishing: electrolysis temperature 50℃, current density 20A / dm³ 2 The electrolysis time is 12 minutes.

[0082] Example 6 The difference from Example 2 lies in the following conditions, while the other conditions remain the same as in Example 2.

[0083] The water pressure for two-phase flow rough polishing is 8 MPa, and the processing time is 15 min. Abrasive flow polishing: average silicon carbide particle size is 22μm, pressure is 3MPa, flow rate is 10m / s, and processing time is 20min; Electrochemical final polishing: electrolysis temperature 50℃, current density 20A / dm³ 2 The electrolysis time is 10 minutes.

[0084] Example 7 The difference from Example 2 lies in the following conditions, while the other conditions remain the same as in Example 2.

[0085] The water pressure for two-phase flow rough polishing is 12 MPa, and the processing time is 20 min. Abrasive flow polishing: average silicon carbide particle size is 18μm, pressure is 5MPa, flow rate is 15m / s, and processing time is 25min; Electrochemical final polishing: electrolysis temperature 60℃, current density 25A / dm³ 2 The electrolysis time is 15 minutes.

[0086] Example 8 The difference from Example 3 lies in the following conditions, while the other conditions remain the same as in Example 3.

[0087] The water pressure for two-phase flow rough polishing is 5 MPa, and the processing time is 10 min. Abrasive flow polishing: average silicon carbide particle size is 14μm, pressure is 2MPa, flow rate is 8m / s, and processing time is 15min; Electrochemical final polishing: electrolysis temperature 30℃, current density 8A / dm³ 2 The electrolysis time is 5 minutes.

[0088] Example 9 The difference from Example 3 lies in the following conditions, while the other conditions remain the same as in Example 3.

[0089] The water pressure for two-phase flow rough polishing is 8 MPa, and the processing time is 15 min. Abrasive flow polishing: average silicon carbide particle size is 14μm, pressure is 3MPa, flow rate is 12m / s, and processing time is 20min; Electrochemical final polishing: electrolysis temperature 40℃, current density 12A / dm³ 2 The electrolysis time is 8 minutes.

[0090] Comparative Example 1 The difference from Example 1 is that two-phase flow rough polishing is not performed, while the remaining steps and conditions are the same as in Example 1.

[0091] Comparative Example 2 The difference from Example 1 is that abrasive flow polishing is not performed, while the remaining steps and conditions are the same as in Example 1.

[0092] Comparative Example 3 The difference from Example 1 is that electrochemical final polishing is not performed, while the remaining steps and conditions are the same as in Example 1.

[0093] Comparative Example 4 The difference from Example 1 is that abrasive flow fine polishing is performed first, followed by two-phase flow rough polishing, while the remaining steps and conditions are the same as in Example 1.

[0094] Experimental Example 1 The inner walls of the initial and final samples in each embodiment and comparative example were dried and subjected to roughness tests (GB / T 1031-2009). The results are shown in Table 1.

[0095]

[0096] As shown in Table 1, compared with Comparative Examples 1-4, Examples 1-9 underwent pretreatment, two-phase flow coarse polishing, abrasive flow fine polishing, and electrochemical final polishing in sequence, which effectively reduced the surface roughness of the inner wall of the final sample and significantly improved the roughness reduction rate of the final sample relative to the initial sample. This makes the samples suitable for various additive manufacturing metal pipelines such as titanium alloys, aluminum alloys, and high-temperature alloys.

[0097] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.

Claims

1. A multi-process combined polishing method for additive manufacturing metal pipe samples, characterized in that, Includes the following steps: S1. Pre-treatment of additive manufacturing metal pipeline samples to obtain initial samples; S2. Two-phase flow rough polishing is performed using two-phase flow to obtain a rough polished sample; S3. Use abrasive flow to perform abrasive flow fine polishing to obtain a finely polished sample; S4. Perform electrochemical final polishing to obtain the final sample; the average particle size of the second abrasive in the abrasive flow is smaller than the average particle size of the first abrasive in the two-phase flow.

2. The multi-process combined polishing method for additive manufacturing metal pipeline samples according to claim 1, characterized in that, The two-phase flow consists of a first abrasive grain and water, wherein the first abrasive grain comprises one or more of boron nitride, aluminum oxide, and diamond.

3. The multi-process combined polishing method for additive manufacturing metal pipeline samples according to claim 2, characterized in that, The mass percentage of the first abrasive grain in the two-phase flow is 10% to 22%. And / or, the average particle size of the first abrasive grain in the two-phase flow is 0.05 to 0.3 mm.

4. The multi-process combined polishing method for additive manufacturing metal pipeline samples according to claim 1, characterized in that, The water pressure for the two-phase flow rough polishing in S2 is 5-12 MPa; And / or, the processing time for the two-phase flow rough polishing in S2 is 10-20 min.

5. The multi-process combined polishing method for additive manufacturing metal pipeline samples according to claim 1, characterized in that, The abrasive flow includes a second abrasive particle and a carrier; the second abrasive particle in the abrasive flow includes silicon carbide and / or aluminum oxide.

6. The multi-process combined polishing method for additive manufacturing metal pipeline samples according to claim 1, characterized in that, The average particle size of the second abrasive grain in the abrasive flow is 10-28 μm; And / or, the mass percentage of the second abrasive grain in the abrasive flow is 40% to 60%.

7. The multi-process combined polishing method for additive manufacturing metal pipeline samples according to claim 1, characterized in that, The pressure for abrasive flow polishing in S3 is 2~5MPa; And / or, the flow rate of the abrasive flow polishing in S3 is 8-15 m / s; And / or, the processing time for abrasive flow polishing in S3 is 15~25 min.

8. The multi-process combined polishing method for additive manufacturing metal pipeline samples according to claim 1, characterized in that, The electrochemical final polishing process in S4 includes: using the finely polished sample as the anode and the lead plate as the cathode, immersing it in the electrochemical polishing solution for electrolysis.

9. The multi-process combined polishing method for additive manufacturing metal pipeline samples according to claim 8, characterized in that, The electrochemical polishing solution comprises sulfuric acid, phosphoric acid, citric acid, and water; And / or, the electrolysis temperature is 30-60℃; And / or, the current density of the electrolysis is 8~25 A / dm³. 2 ; And / or, the electrolysis time is 5~15 min.

10. The multi-process combined polishing method for additive manufacturing metal pipeline samples according to claim 1, characterized in that, The final sample exhibits a roughness reduction rate of ≥97% relative to the initial sample.